2017
DOI: 10.1038/s41598-017-01332-z
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Blimp1 transcriptional repressor unleashes p130Cas/ErbB2 breast cancer invasion

Abstract: ErbB2 overexpression is detected in approximately 20% of breast cancers and is correlated with poor survival. It was previously shown that the adaptor protein p130Cas/BCAR1 is a crucial mediator of ErbB2 transformation and that its overexpression confers invasive properties to ErbB2-positive human mammary epithelial cells. We herein prove, for the first time, that the transcriptional repressor Blimp1 is a novel mediator of p130Cas/ErbB2-mediated invasiveness. Indeed, high Blimp1 expression levels are detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Blimp1 is a transcriptional repressor that controls gene expression changes in B-cell-to-plasmablast transition, which led to silences of B-cell gene expression in PC ( 59 ). High Blimp1 expression tends to trigger BC cell invasion and metastasis formation ( 60 ). Thus, targeting B-cell transcriptional regulators may further influence BC progression and invasiveness, which reinforces the potential of B cells as a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Blimp1 is a transcriptional repressor that controls gene expression changes in B-cell-to-plasmablast transition, which led to silences of B-cell gene expression in PC ( 59 ). High Blimp1 expression tends to trigger BC cell invasion and metastasis formation ( 60 ). Thus, targeting B-cell transcriptional regulators may further influence BC progression and invasiveness, which reinforces the potential of B cells as a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…impair tumor invasiveness in vitro and lung metastasis formation in vivo [39]. In addition, PRDM1 expression positively correlates with a higher probability of developing multiple metastasis in patients with high p130Cas, supporting the major role played by p130Cas in Blimp1-mediated invasion [39].…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, a later study demonstrated that PRDM1/BLIMP1 played an essential role in transforming growth factor (TGF)-β1-induced epithelial-mesenchymal transition (EMT) signature and cell migration of breast cancer cells via BMP-5 repression ( Figure 1B) [38]. Additionally, both in vitro and in vivo models have recently described the role of PRDM1/Blimp1 in p130Cas/ErbB2 breast cancer invasion; particularly, Blimp1 was highly expressed during p130Cas/ErbB2 dependent invasion in breast cancer cells and the downregulation of its expression was sufficient to severely impair tumor invasiveness in vitro and lung metastasis formation in vivo [39]. In addition, PRDM1 expression positively correlates with a higher probability of developing multiple metastasis in patients with high p130Cas, supporting the major role played by p130Cas in Blimp1-mediated invasion [39].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations